Editor's Note (Cistercian studies quarterly, 2009)
The article discusses the declaration of Fr. Chrysogonus Waddell as the most important and incisive scholar of Cistercian. The author asserts that it was made with full conviction in an informal context by Brian Patrick McGuire, an international scholar of medieval Cistercian history. He states that according to an article, many monks and nuns were exposed to the spiritual potential of the early Cistercian documents, but were neglected, until Chrysogonus dedicated himself to make them known.